Evaluation of cylinder shape solar dryer on natural convection heat transfer - Susuk, Sriwichai; Visutthipat, Rachain; Inchoorrun, Natsacha; Promjan, Weerayuth (Journal of Applied Research on Science and Technology (JARST), 2025)
This research supports that renewable energy sources were used to power the drying process for design in a solar dryer, leading to the preservation of agricultural products and suitable preservation systems. The drying system involves complex physical atmospheric mechanisms, with relations between the dry air and the moisture content of each product, which affect the performance of solar drying systems. Steady laminar natural convection heat transfer formulas that are accurate based on a boundary-layer have been used to evaluate the flow caused by nonuniform density in an air flow based on dimensionless equations, and natural flow (buoyancy) inside the indirect solar dryer. Results show the heat transfer coefficient for natural convection 5 – 6 W/m2°C, heat energy 25 - 65 J/s, collector efficiencies 29 - 40.6 % and drying rate 0.18 - 0.98 kg/hr. The heat and mass increased according to dry-air flow through the dryer under trends of solar radiation 312 - 513 W/m2 and temperatures inside the indirect solar dryer 39.7 - 53.7°C, respectively, as ambient temperature 30.5 - 42.5°C, relative humidity 36 - 52% schedule 08:00 a.m. - 04:00 p.m. (daylight clear sky recorded). Experimentation, a test with a similar climate condition, with an initial moisture content of 85% to the final moisture content of 15% on a wet basis, showed a drying rate of 0.08 - 0.19 kg/hr.